2013
DOI: 10.1589/jpts.25.317
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dual-Motor Task Training on the Gait Ability of Chronic Stroke Patients

Abstract: Abstract. [Purpose] This study examined the effects of consecutive training in dual motor tasks on the gait ability of chronic stroke patients. [Subjects and Methods] Conservative physical therapy was conducted for 29 subjects divided into two groups. The dual-motor task group was also taught a basic motor task and additional motor tasks, whereas the single-motor task training group was taught consecutive single motor tasks. Both groups performed their programs five times a week for 30 minutes over a period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…Yang et al 6 ) reported that dual-task training is effective for improving gait speed, stride, and time. Studies by An et al 9 ) and Kim et al 16 ) showed that dual-task training improved gait ability in the experimental group. Although there were differences in the experimental environment, the advanced studies and this study have similar results.…”
Section: Discussionmentioning
confidence: 94%
“…Yang et al 6 ) reported that dual-task training is effective for improving gait speed, stride, and time. Studies by An et al 9 ) and Kim et al 16 ) showed that dual-task training improved gait ability in the experimental group. Although there were differences in the experimental environment, the advanced studies and this study have similar results.…”
Section: Discussionmentioning
confidence: 94%
“…Tyrimo rodikliai sutampa su kitų autorių gautaisiais. Nustatyta, kad dvigubos užduoties metodas yra efektyvesnis už bazinę kineziterapiją, lavinant asmenų, patyrusių insultą, eiseną (Kim et al, 2013;Liu et al, 2017) ir po galvos smegenų traumų (Rahman et al, 2018). Mokslininkų teigimu (Shin, An, 2014), egzistuoja glaudus ryšys tarp pusiausvyros ir funkcinio mobilumo, todėl pagerėjusi pusiausvyra tiesiogiai teigiamai veikia judėjimo galimybes.…”
Section: Rezultatų Aptarimasunclassified
“…There are several studies conducted on investigating the recovery of gait abilities, one of them being focused on the performance of dual-task training to improve gait and balance [2,3,9]. Dual-task training is comprised of the performance of one basic task with the addition of one or another task simultaneously [11]. Current studies with stroke patients have shown improvements in gait velocity, stride length, cadence and other spatio-temporal parameters [12].…”
Section: Introductionmentioning
confidence: 99%
“…If automatic movement arises through repetitive gait training, the effectiveness of cognitive interference training, dual-task performance focused on task-oriented gait training may improve gait speed and coordination [17,18]. In addition, other studies have reported the improvement of gait and balance through training with use of a ball or rings, or obstacle courses or the performance of dual-task training with virtual reality have reported improved balance and gait in persons affected by stroke [9,11,12,15,16]. Wulf et al [19] reported that training with use of a balance pad and/or similar equipment using an external focus was more effective on producing postural control compared to training with an internal focus using one's ankles.…”
Section: Introductionmentioning
confidence: 99%